Construction of Islamic Boarding Shcool in Developing Moderate Islam - Siti Yumnah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Islamic teachings are moderate teachings as set out in the Koran. However, at the level of practice, Islam sometimes becomes radical and sometimes becomes liberal. This is because of the lack of in-depth Islamic knowledge. Therefore, this study examines the construction of Islamic thought, develops moderate Islam. Based on the analysis of literature and field facts, moderate Islam in pesantren is inseparable from the Wali Songo who spread the religion of Islam in the archipelago by (1) maintaining the balance of fiqh reasoning and Sufism, (2) making the theology of Ahlussunah a monotheistic approach, (3) maintaining traditions that exist in the community. The pesantren develops (1) values ​​in caring for the understanding of Islamic religious thought, (2) values ​​in caring for the understanding of thought among religious people, (3) values ​​in caring for religious and cultural understanding. These values ​​are always maintained and preserved by pesantren in the process of religious thought, education and preaching.